Defining capacity building in the context of HTA: a proposal by the HTAi Scientific Development and Capacity Building Committee. (11th September 2019) - Pichler, Franz; Oortwijn, Wija; Ruether, Alric; Trowman, Rebecca
Abstract: Objectives: To develop a definition of "capacity building" relevant to Health Technology Assessment international (HTAi). Methods: A review of capacity building activities undertaken by HTAi members, members of the International Network of Agencies for Health Technology Assessment (INAHTA), and regional HTA networks was compared against general literature on capacity building definitions and frameworks. The findings were reviewed by the HTAi Scientific Development and Capacity Building Committee. Furthermore, the Executive Committee and Interest Groups of HTAi provided input on the draft final paper. Results: The literature demonstrated the need for a definition of capacity building specific to HTA. In the context of HTAi, it was necessary for the definition to cover (i) the broadest range of HTA-related activities, (ii) multiple stakeholders involved in the HTA process, and (iii) the spectrum of activities that compose capacity building. We propose the following definition of HTA capacity building: The process by which individuals and organizations develop or strengthen abilities related to understanding, providing input to, conducting, or utilizing HTA for health policy and decision making, as well as, developing awareness and support in the environment within which HTA is being used. Conclusion: A definition of HTA-related capacity building that was intended to provide clarity about what this term means to HTAi was developed. As HTA is context-dependent, a need for further work to develop an operationalization "menu" relevant to the specific needs in which HTA is being used was identified.